UV/sulfite chemistry to reduce N-nitrosodimethylamine formation in chlor(am)inated water - Seid, Mingizem Gashaw; Cho, Kangwoo; Hong, Seok Won (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
The disinfection by-product N-nitrosodimethylamine (NDMA) is a major concern in water quality management due to its carcinogenicity. Thus, a proper pretreatment is necessary to mitigate NDMA formation upon periodic chloramination by removing precursors, such as ranitidine (RNT). This study investigated the effect of UV/sulfite pretreatment on NDMA formation from an RNT-spiked tap and chloraminated synthetic swimming pool (SSP) water. At UVC intensity of 2.1 mW cm(-2) and 0.5 mM of sulfite, UV/sulfite chemistry showed complete degradation of 20 mu M RNT within 30 min. It was found that SO4 center dot- primarily reduced the NDMA formation potential (FP) of RNT, while hydrated electrons effectively mitigated the pre-formed NDMA in the SSP water. The UV/sulfite pretreatment alleviated NDMA formation during post-chloramination (24 h) by up to 82%, outperforming the commonly employed advanced oxidation processes such as UV/H2O2. However, in the presence of bromide ions, the effectiveness of UV/sulfite pretreatment was seriously deteriorated, although the bromide ion itself was found to inhibit the NDMA formation from RNT especially at pH < 8 during chloramination. Mass spectrometric analysis indicated that the NDMA-FP of RNT could be removed by UV/sulfite principally via N-methylation, dealkylation, and oxygen transfer pathways. Consequently, UV/sulfite could be used as an alternative unit process for water treatment with reduced NDMA formation. (C) 2020 Elsevier Ltd. All rights reserved.